2018
DOI: 10.7150/thno.23453
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Markers and Mediators in Sepsis

Abstract: Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. It remains a highly lethal condition in which current tools for early diagnosis and therapeutic decision-making are far from ideal. Extracellular vesicles (EVs), 30 nm to several micrometers in size, are released from cells upon activation and apoptosis and express membrane epitopes specific for their parental cells. Since their discovery two decades ago, their role as biomarkers and mediators in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 165 publications
0
130
0
4
Order By: Relevance
“…Microvesicles are known determinants of venous thromboembolism [6]. Indeed, increased numbers of circulating microvesicles have been reported in septic patients [7] and it is therefore possible that…”
Section: Accepted Articlementioning
confidence: 99%
“…Microvesicles are known determinants of venous thromboembolism [6]. Indeed, increased numbers of circulating microvesicles have been reported in septic patients [7] and it is therefore possible that…”
Section: Accepted Articlementioning
confidence: 99%
“…As mentioned earlier, multiple studies pointed out the significant differences in the contents of exosomes released by macrophages under different conditions . This indicated that exosomes released under different conditions might be involved in different functions and pathological processes.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, the protein cargo of exosomes is related to specific cell type and confer features to these exosomes . The existing evidence suggests that extracellular vesicles (EVs) derived from circulating cells such as neutrophilic granulocytes, macrophages, dendritic cells (DCs), and natural killer (NK) cells have an important role as mediators in sepsis . Several protective EV‐related mechanisms were recently revealed, while some EVs from leukocytes can be harmful in sepsis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of EVs can be internalized by other cells and thus influence the function of recipient cells. Because of these characteristics, the diagnostic and therapeutic utility of EVs has been studied extensively [100][101][102]. Different types of EVs have been defined based on their size, origin, and function, e.g., microvesicles, microparticles, exosomes, and apoptotic bodies [103].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%